The Impact of the Pandemic on E-Learning and Its Evolution: A Mixed-Methods Study - Iyer, Ravi (Global journal of Business and Integral Security, 2025)
In the past few years, technology has significantly transformed countries across the world. Technology has affected our lives in many aspects, particularly in terms of learning methods. E-learning provides the globalization of education, allowing learners from various parts of the world to access education regardless of location with an internet connection. The education sector has experienced a drastic change with the emergence of e-learning as a major part of the modern education system. The occurrence of the pandemic has affected the world severely, including the education system. Online learning offers many advantages to students in regulating their education in crisis time. The present study executes mixed method research methodology where quantitative analysis utilizes the SPSS version 23 software package. A structured questionnaire survey technique is utilized to gather the data from students and teachers. Qualitative analysis was conducted using the interview technique. Purposive sampling strategy has been adopted for analysis. The objective behind the technique is to gather data relating to the perception of students and teachers regarding e-learning and its growth in the time of the pandemic. Descriptive statistics, Independent sample T-test, ANOVA, Regression, correlation, and frequency tests are performed in research. The outcomes of the study revealed that there is a significant impact of a pandemic on e-learning in higher education, and online learning has evolved due to the pandemic, and there is an implication for the future of higher education. Furthermore, the study also indicates the prevalence of challenges and opportunities for e-learning in the context of the pandemic. The current study concludes that the effectiveness and the value of e-learning impact the perception of students and faculty. As technology advances, it is evident that e-learning will play an increasingly important role in the education sector.